2003
DOI: 10.1046/j.1365-2672.2003.01829.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of benzyldimethylalkylammonium chloride by Aeromonas hydrophila sp. K.

Abstract: Aims: The aim of this work was to study the biodegradation of benzyldimethylalkylammonium chloride (BAC) by Aeromonas hydrophila sp. K, an organism isolated from polluted soil and capable of utilizing BAC as sole source of carbon and energy. Methods and Results: High performance liquid chromatography and gas chromatography–mass spectrometry (GC‐MS) analysis was used to study BAC degradation pathway. It was shown that during BAC biodegradation, formation of benzyldimethylamine, benzylmethylamine, benzylamine, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 14 publications
6
87
1
2
Order By: Relevance
“…(iii) Furthermore, microbial communities such as those established in the microcosms might physically bind or chemically degrade QAC, thereby ameliorating or considerably reducing lethality. In these respects, the degradation of the QAC benzyldimethylalkylammonium chloride has been reported for Aeromonas hydrophila (36), and since A. hydrophila was a major species within the drain microcosms, QAC degradation is a possibility. DGGE analysis of short-term microcosms.…”
Section: Resultsmentioning
confidence: 95%
“…(iii) Furthermore, microbial communities such as those established in the microcosms might physically bind or chemically degrade QAC, thereby ameliorating or considerably reducing lethality. In these respects, the degradation of the QAC benzyldimethylalkylammonium chloride has been reported for Aeromonas hydrophila (36), and since A. hydrophila was a major species within the drain microcosms, QAC degradation is a possibility. DGGE analysis of short-term microcosms.…”
Section: Resultsmentioning
confidence: 95%
“…Nitrates and ammonium are abundant in Lascaux Cave (Lastennet et al, 2009), and it is expected that nitrites are as well; however, the last was not analysed. When benzalkonium chloride is degraded by bacteria, formation of benzyldimethylamine, benzylmethylamine, benzylamine, benzaldehyde and benzoic acid occurs (Patrauchan & Oriel, 2003). Nobuo (2005) found that a Scolecobasidium sp.…”
Section: The Black Stainsmentioning
confidence: 99%
“…Pseudomonads have also been reported to utilize dodecyldimethylamine (20) and hexadecyltrimethylammonium chloride (43). In addition, Acinetobacter sp., Serratia marcescens, and Aeromonas hydrophila have also been reported to degrade QACs (1,29,36). It is probable that the Pseudomonas sp., Serratia sp., and Aeromonas hydrophila isolates identified in this study as carrying class 1 integrons are involved in QAC degradation.…”
Section: Vol 49 2005 Integron Incidence In a Qac-polluted Environmementioning
confidence: 99%